The Effect of Budgetary Control on Financial Performance of Public Universities in Mount Kenya Region, Kenya - KAWIRA, LILIAN (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Managers use budgetary control to match financial performance objectives with budgets, compare budgets with the actual outcomes, and implement essential modifications. Attaining robust financial performance stands as a fundamental goal for any prosperous organization. Nonetheless, public universities in Kenya persist in encountering obstacles in their financial performance. The main objective of the research was to establish the effect of budgetary control on the financial performance of public universities located in the Mount Kenya Region of Kenya. The specific objectives for the study were; to establish the effect of budget planning, budget implementation, budget monitoring and budget participation on financial success of the public universities in Mount Kenya region. This research majorly used the hypothesis of budgeting, the agency hypothesis and the stakeholder’s hypothesis. The design used in the investigation was descriptive. The target population was 7 universities located in Mount Kenya Region. The specific respondents were the 284 heads of departments in both Academic and Administration divisions of the universities. Since the target population was small, all the 284 respondents were used in the study. Collection of data for this study was conducted through the implementation of structured questionnaires. The researcher used drop and pick method to issue and collect filled in questionnaires after 2 weeks. Data analysis was performed to establish a link between theory and reality by examining the research hypothesis and addressing the study objectives. The clean data were entered in the SPSS for further analysis. These data were analyzed using descriptive techniques, correlations and regressions. The analyzed data were presented by use of the charts and tables. The study results showed that budgetary planning had a positive and significant effect on financial performance of public universities. Further results showed that budgetary participation had a positive and significant effect on financial performance of public universities. In addition, results showed that budgetary monitoring had a positive and significant effect on financial performance of public universities. Further results showed that budgetary implementation had a positive and significant effect on the financial performance of public universities. The study concluded that most public universities were not able to fully involve their employees in the budgetary process. Further, most public university employees are not committed to ensuring an effective budget process. The study concluded that though the public universities had budgetary committees the committees were not able to periodically meet and review the budget performance. In addition, most public universities budget policies were not able to help in monitoring budget spending limits. The study concluded that most public universities were not always able to audit their report. Further, the evaluation process of the budgets in most universities was not transparent. Further, budget auditing enhanced the performance of the institutions. Further, effective communication and transparency during the budgetary process enhanced the financial performance of the universities. Universities must work with budgetary control techniques that contribute significantly to improving the financial performance of universities because of their effectiveness. Therefore, to improve the budgetary control measures, it is recommended that the university give wide attention to developing budgetary control through proper planning, monitoring, and implementation of the budgets as well as allowing the participation of employees in the budget process.